MECHANICAL AND METALLOGRAPHIC TESTS OF CASING OF AUTOMOBILES MAZ CAGE - V. A. Gurinovich; L. A. Isaevich; M. I. Sidorenko (Литьë и металлургия, 2011)
It is shown that cover case of automobile cage, produced by means of crimp seal of steel seamless pipe billet, is the most preferable by its manufacturability and high cyclic endurance of ready article.